2018
DOI: 10.1002/ece3.4483
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity explains maximum variation in productivity under experimental warming, nitrogen addition, and grazing in mountain grasslands

Abstract: Anthropogenic global warming, nitrogen addition, and overgrazing alter plant communities and threaten plant biodiversity, potentially impacting community productivity, especially in sensitive mountain grassland ecosystems. However, it still remains unknown whether the relationship between plant biodiversity and community productivity varies across different anthropogenic influences, and especially how changes in multiple biodiversity facets drive these impacts on productivity. Here, we measured different facet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 67 publications
(102 reference statements)
1
16
0
Order By: Relevance
“…In contrast to the branch length‐based metrics, several phylogenetic diversity metrics (e.g., PAE, the relationship between species evolutionary distinctiveness and abundance; IAC, the imbalance of abundances at higher clades) have been developed to capture information on both the topology and branch lengths of phylogenies connecting the species of a community (Cadotte et al, ; Krajewski, ; Vanewright, Humphries, & Williams, ). These topology‐based metrics have also been shown to be valuable for predicting patterns of abundance, community composition, and ecosystem functioning (Cadotte et al, ; Liu et al, ; Liu, Zhang, et al, ), but are seldomly evaluated in terms of how the branch lengths and topologies of community phylogenies may affect estimates of community phylogenetic diversity. Here, we predict that the use of a backbone phylogeny will have a strong influence on topology‐based metrics.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the branch length‐based metrics, several phylogenetic diversity metrics (e.g., PAE, the relationship between species evolutionary distinctiveness and abundance; IAC, the imbalance of abundances at higher clades) have been developed to capture information on both the topology and branch lengths of phylogenies connecting the species of a community (Cadotte et al, ; Krajewski, ; Vanewright, Humphries, & Williams, ). These topology‐based metrics have also been shown to be valuable for predicting patterns of abundance, community composition, and ecosystem functioning (Cadotte et al, ; Liu et al, ; Liu, Zhang, et al, ), but are seldomly evaluated in terms of how the branch lengths and topologies of community phylogenies may affect estimates of community phylogenetic diversity. Here, we predict that the use of a backbone phylogeny will have a strong influence on topology‐based metrics.…”
Section: Introductionmentioning
confidence: 99%
“…Intraspecific trait variation captures phenotypic plasticity and is increasingly recognized as important for coexistence dynamics (Violle et al, 2012). Several studies have shown that intraspecific trait variation may be more important for short‐term responses than species turnover (Jung et al, 2014; Liu et al, 2018b). As experimental treatments were applied only two years prior to this study, it is thus possible that we were not able to detect functional responses to treatments because we did not measure intraspecific trait variation at the whole‐community level.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the two focal species at White Gum (the lower site) did not experience a change in the net effect of neighbours. These were the only annual species ( Trifolium subterraneum ) and the focal species with a “climber” growth form ( Convolvulus erubescens ), suggesting that plants of certain functional types or life histories may be differentially impacted by warming (Liu et al, 2018). A more likely explanation, however, is that current environmental conditions mediate the effect of future climate changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast with our expectation that the functional/phylogenetic diversity-productivity relationship would be more robust and more consistent than the taxonomic diversity-productivity relationship at both local and regional scales. A number of studies have reported the signi cance of functional/phylogenetic diversity over taxonomic diversity in explaining variation in plant productivity (Cadotte et al 2009;Flynn et al 2011;Liu et al 2015Liu et al , 2018). Our results showed that the top-ranked single models for all local scales that included either functional diversity or phylogenetic diversity generally agree with previous studies.…”
Section: Scale-dependency Of Explaining the Variation In Plant Producmentioning
confidence: 99%